1999
DOI: 10.1016/s0042-6989(98)00258-2
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of accommodation toward apparent depth

Abstract: This paper deals with characteristics of accommodation evoked by perceived depth sensation and the dynamic relationship between accommodation and vergence, applying newly developed optical measurement apparatuses. A total of five subjects looked at three different two-dimensional stimuli and two different three-dimensional stimuli; namely a real image and a stereoscopic image. With regard to the two-dimensional stimuli, a manifest accommodation without any accompanying vergence was found because of an apparent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 26 publications
3
27
0
Order By: Relevance
“…6 Ocular Near Triad Accommodation, vergence, and pupillary dynamics, i.e., the ocular near triad, continuously interact to control the functioning of the eyes. 7 To obtain clear, binocular single vision, our eyes are accommodated and converged by an amount that depends on the distance between us and the object of interest. Vergence can be defined as movement of our eyes in opposite directions to locate the area of interest on the fovea and accommodation as alteration of the lens to obtain and maintain the area of interest focused on the fovea.…”
Section: Human Perception Of Depth Binocular Depth Perceptionmentioning
confidence: 99%
“…6 Ocular Near Triad Accommodation, vergence, and pupillary dynamics, i.e., the ocular near triad, continuously interact to control the functioning of the eyes. 7 To obtain clear, binocular single vision, our eyes are accommodated and converged by an amount that depends on the distance between us and the object of interest. Vergence can be defined as movement of our eyes in opposite directions to locate the area of interest on the fovea and accommodation as alteration of the lens to obtain and maintain the area of interest focused on the fovea.…”
Section: Human Perception Of Depth Binocular Depth Perceptionmentioning
confidence: 99%
“…The vergenceaccommodation conflict is indeed an old issue that has been investigated by numerous studies [7], [10]- [13]. In the 90's, the research groups in [10], [11] reported that, in stereoscopic 3-D viewing, the vergence-accommodation conflict was one of the factors in determining visual discomfort and fatigue. Recent studies have provided empirical evidence that the vergence-accommodation conflict can cause visual discomfort and fatigue [4], [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…While changing vergence, the viewer is forced to maintain accommodation at a static level to keep the screens in focus. Takeda et al (1999) found significant amounts of accommodation to stereoscopic images in a simulated virtual display. In keeping with the findings by Takeda and colleagues, Inoue and Ohzu (1997) found that pronounced accommodation responses occur when viewing stereo pairs.…”
Section: Stereoscopic Displays Disrupt Accommodation-vergence Linkagementioning
confidence: 86%